Molecular Dynamics Study on the Encapsulation of Prilocaine in Liposomes at Physiological pH - Giupponi, Giovanni (2013)
In this work, we investigated the concentration effects on the encapsulation of prilocaine (PLC), an aminoamide local anesthetic, into a small unilamellar liposome, at physiological pH. On the line of our previous work, we have carried out Molecular Dynamics (MD) simulations using a coarse grain (CG) model that allow us to reach the microsecond time scale. At physiological pH there is a partition between protonated and neutral PLCs. In order to estimate the protonated/neutral PLC ratio at physiological pH (7.4), we have used the Henderson-Hasselbach equation. We have studied three PLC:lipid molar concentrations, ranging between 10:10 to 1:4. We essentially found that all neutral PLC molecules rapidly diffuse into the hydrophobic region of the vesicle adopting an asymmetric bimodal distribution. Moreover, protonated PLC molecules partition between the external monolayer of the vesicle and the water phase, having a high rate of exchange between this two phases, with no access to the inner part of the liposome in a concentration dependent way. In this way, we found that the behavior of PLCs at physiological pH is a combination of high and low pH, especially at low concentration of local anesthetics.